Kinase inhibitor pharmacokinetics: comprehensive summary and roadmap for addressing inter-individual variability in exposure. (2nd January 2017) - Rowland, Andrew; van Dyk, Madelé; Mangoni, Arduino A.; Miners, John O.; McKinnon, Ross A.; Wiese, Michael D.; Rowland, Angela; Kichenadasse, Ganessan; Gurney, Howard; Sorich, Michael J.
ABSTRACT: Introduction: Small molecule protein kinase inhibitors (KIs) are a class of drugs with complex and unconventional physiochemical and pharmacokinetic characteristics. Cytochrome P450 mediated metabolism and transporter-mediated uptake and efflux are important processes that determine KI disposition and exposure. Areas covered: We provide an overview of KI pharmacology, with a comprehensive summary of KI physiochemical and pharmacokinetic properties and description of the major sources of variability in KI pharmacokinetics focusing on common pathways involved in determining exposure. We also consider the strategies proposed to optimize KI dosing, appraise the current evidence for their use and analyze the challenges and knowledge gaps for KI dose optimization. Expert opinion: A number of strategies to optimize KI dosing have been proposed, but evidence underpinning their use is limited. The major challenge for optimized KI dosing is the development of high-quality evidence to demonstrate a significant improvement in therapeutic outcomes and /or reduction in adverse events through appropriately designed trials in a setting where the limited KI prescribing restricts capacity to undertake prospective randomized studies. If precision KI dosing can facilitate a fraction of the reported observational benefits, then substantial gains in patient outcomes will be derived in a cost-effective manner.